Demons and Angels: Morality Plays in the Context of Salesian Educational Theatre for Young Women - Cavallaro, Daniela (The international journal of religion and spirituality in society, 2013)
Since the time of Don Bosco (1815-1888), theatre has been an essential part of the preventive system of education of the youth offered by the Salesians of Don Bosco and the Salesian sisters. After the fall of Italian Fascism and the end of WWII, educational theatre acquired further importance for the instruction of girls and young women as it aimed to counteract the potential challenge to the centrality of the Catholic home and family constituted by the sexually empowered female characters presented by Italian and American cinema. In this article I discuss the theatrical production that the Salesian sisters wrote and staged for the education and entertainment of the female community (convents, schools, and oratories) which revolved around their order. After briefly summarising the variety of theatrical genres that they used, I focus in particular on the numerous plays based precisely on the moral threats constituted by the media (cinema, glossy magazines and paperback novels) and pastimes such as dancing on the moral upbringing of young women.